DARI PIRING KE PRESTASI: DAMPAK MAKANAN BERGIZI GRATIS DI SEKOLAH DASAR - Ahmad Tarmizi Hasibuan; Torkis Dalimunte; Sahlan (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
The free nutritious meal program in elementary schools is a crucial strategy for addressing nutritional deficiencies and supporting improved student learning. This study aims to explore in depth the experiences, perceptions, and impacts of the free, nutritious meal program on students' learning readiness and Well-being. A qualitative approach using desk research methods was used to analyse academic literature, reports, and policies related to nutrition interventions in schools. The analysis was conducted using a descriptive and inductive approach, grouping findings into relevant themes. The free nutritious meal program is an investment in human capital that has the potential to strengthen the foundations of elementary school children's health, cognitive development, and education. Effective implementation requires strong governance, school community involvement, and sustainable policies. Further research is needed to assess the long-term impacts and better understand students' experiences. This study concludes that the free nutritious meal program functions as a multidimensional intervention that supports human capital development from an early age. Research implications include the importance of improving program governance, strengthening regulations, and integrating nutrition and education policies. Further research is recommended to examine the long-term impacts and develop implementation models that are more adaptive to local contexts.